Ploidy-altered phenotype interacts with local environment and may enhance polyploid establishment in Knautia serpentinicola (Caprifoliaceae) - Čertner, Martin; Sudová, Radka; Weiser, Martin; Suda, Jan; Kolář, Filip (The New phytologist, 2019)
Whole genome duplication is a key process in plant evolution and has direct phenotypic consequences. However, it remains unclear whether ploidy-related phenotypic changes can significantly alter the fitness of polyploids in nature and thus contribute to establishment of new polyploid mutants in diploid populations. We addressed this question using a unique natural system encompassing a diploid and its sympatric locally established autotetraploid derivative. By setting a common garden experiment with two manipulated environmental factors (presence/absence of serpentine substrate and competition), we tested whether these two locally important factors differently shape the phenotypic response of the two ploidy levels. Tetraploids attained significantly higher values of both above- and below-ground biomass, and root : shoot ratio compared to their diploid progenitors. Tetraploid superiority in vegetative fitness indicators was most prominent when they were cultivated together with a competitor in nutrient-rich nonserpentine substrate. We show that even genetically very closely related diploids and tetraploids can respond differently to key environmental factors. Provided there are sufficient nutrients, tetraploids can be more successful in tolerating interspecific competition than their diploid progenitors. Such superior performance might have provided an adaptive advantage for the newly established tetraploid promoting colonisation of new (micro-)habitats, which was indeed observed at the natural site.
Keywords: genome duplication; Polyploidy; Genome, Plant; diploidie; ekosystém; Diploidy; Sympatry; genom rostlinný; interspecific competition; fenotyp; Caprifoliaceae; ploidie; Phenotype; Ploidies; ploidy coexistence; Environment; polyploid establishment; sympatrie; tetraploidie; Tetraploidy; serpentine; životní prostředí; Ecosystem; polyploidie